EFFECT OF SAFETY VALVES AND HOLE DIAMETER STOVE AGAINST BIOGAS FLAME - Harie Satiyadi Jaya; Jhonni Rentas Duling (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2015)
Problem of rural communities in Indonesia is difficult to obtain kerosene on the market. Team researchers have tried to provide a solution by building a biogas digester type